2016
DOI: 10.3390/rs8030185
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Modeling of the Urban Heat Island in the Phoenix Metropolitan Area: Land Use Change Implications

Abstract: This study examines the spatial and temporal patterns of the surface urban heat island (SUHI) intensity in the Phoenix metropolitan area and the relationship with land use land cover (LULC) change between 2000 and 2014. The objective is to identify specific regions in Phoenix that have been increasingly heated and cooled to further understand how LULC change influences the SUHI intensity. The data employed include MODerate-resolution Imaging Spectroradiometer (MODIS) land surface temperature (LST) 8-day compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 50 publications
(42 reference statements)
6
68
1
Order By: Relevance
“…The correlation analysis results (Table 2) also show the same results. This finding is consistent with some other studies [1,51,54].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The correlation analysis results (Table 2) also show the same results. This finding is consistent with some other studies [1,51,54].…”
Section: Discussionsupporting
confidence: 83%
“…Many researches have been concentrated on the relationship between land-use/cover and surface temperature [1,[51][52][53][54], but they have ignored the mixed pixel in the image. In our research, we focus on the relationship between ULSMFs fractions and LSBT, which means that we classified one pixel into three components and analysed the relationship between the fractions and LSBT, achieving an accuracy of 98.6% in multivariate regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We further compared the urban area extracted using nighttime data with that from Landsat data (maximum likelihood classification method). The results showed that the urban area extracted using the method in this study was larger than that from Landsat data ( Table 2); however, it is appropriate for this study due to these reasons: (a) the footprint of SUHI was larger than the actual urban size according to previous studies [40,48,49]; (b) the urbanization primarily occurred in the suburban areas according to previous studies [26,36]; (c) the study period in this study was 2001-2016, the land cover maps used were during 2001-2013, and the urban area may expand during 2014-2016. Finally, we generated the buffer zone between 20 and 25 km from the urban areas, and we excluded the pixel with DN > 10 (SNLD) in the 20-25 km buffer and defined it as rural area [5,41].…”
Section: Extraction Of Urban Areamentioning
confidence: 46%
“…These results were similar to previous studies [3,10,32] and can be attributed to vegetation activities. Vegetation can release more latent heat fluxes but less sensible heat fluxes (than the artificial impervious surfaces: roads and buildings) by evapotranspiration and then decrease the temperature [3,26,35]. However, rapid urbanization transformed the cropland and forest to impervious surfaces, decreasing the vegetation coverage and increasing the SUHII.…”
Section: -Year Averaged Ues On Vegetation and Suhiimentioning
confidence: 99%
See 1 more Smart Citation